The Relationship Between Dietary Patterns And Nutritional Status Among Female Adolescents At SMK Negeri 8 Pekanbaru - dini, Brilian; Lubis, Tsalasya Naswa; Juwita, Sellia (Jurnal Maternitas Kebidanan, 2025)
Nutritional status is one of the important indicators in determining adolescent health. Poor eating patterns can disrupt body metabolism, affect appetite, and impact energy balance, thus potentially altering nutritional status. This study aimed to determine the relationship between eating patterns and nutritional status among female adolescents at SMK Negeri 8 Pekanbaru in 2025. This research employed an analytic design with a cross-sectional approach. The study sample consisted of 184 female adolescents selected using a total sampling technique. Data on eating patterns were collected using a questionnaire, while nutritional status was measured based on Body Mass Index (BMI) according to WHO standards. Data analysis was carried out univariately and bivariately using the chi-square test with a significance level of 0.05. The findings showed a significant relationship between eating patterns and nutritional status among female adolescents at SMK Negeri 8 Pekanbaru. This means that adolescents with good eating patterns tend to have normal nutritional status, as proven by the research results with a p-value = 0.000 < 0.05. There is a significant relationship between eating patterns and nutritional status among female adolescents at SMK Negeri 8 Pekanbaru. Adolescents with poor eating patterns are more likely to have abnormal nutritional status.